Penerapan Multi Sensor Berbasis ESP8266 dalam Pengembangan Sistem Pemantauan Siswa di Sekolah - Pradnyaditha, Kadek Yoga Vidya; Ngurah Eka Karyawati, Anak Agung Istri (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 1 (2024): JELIKU Volume 13 No 1, August 2024, 2024)
This study develops a student monitoring system with multi-sensor based on ESP8266 to monitor student attendance and location at school. Data from RFID sensors are collected, processed, and displayed on a created website page. After testing, the results indicate that the server data logger system performs optimally during the night, with an average response time of 55 seconds and a peak transmission speed of 0.6 cards per second. In the morning, the average response time is 116.9 seconds with a peak transmission speed of 0.2 cards per second, while during the day, the average response time reaches 96.8 seconds with a peak transmission speed of 0.23 cards per second. Additionally, t-test results indicate that there is no significant difference in data speed between client and server data-logger configurations. Web feature testing also demonstrates that the overall system operates according to the established test cases, with the tested functionality of the attendance website functioning well and usable.